(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Thesis focuses on improving the quality of education in the field of genetics in secondary schools, the development of scientific potential of students, as well as interdisciplinary interdependence in teaching students to solve problems in genetics in our colleagues who teach biology in schools. There are some problems that make it difficult for students to acquire genetic knowledge in the educational process and suggestions for their solution